Raciocínio emocional e regulação afetiva numa perspectiva desenvolvimental na infância - Santos, Simone Aparecida dos (2005)
This study investigated the occurrence of emotional reasoning in childhood, while a natural phenomenon of development, as well as forms of emotional regulation (ER) and perceived physiological sintomatology perceived when facing emotions of fear. We also assessed the relationships of these variables with stress level, intellectual level, sex and age for a nonclinical sample of pre- and primary school children of two schools (public and private) (n = 112; age group between 6 and 10 years old). The children were tested, initially, starting from the Scale of Infantile Stress and Raven's Colored Progressive Main Test. Later, when facing eight scripts/stories involving threat and safety information for two context types (social interaction and physical integrity), the participants gave answers in the categories physiological symptoms, danger degree (evaluation of the emotional reasoning) and strategies of ER. The results revealed a significant correlation between the physiological sintomatology and fear for all the scripts, confirming the occurrence of emotional reasoning for this sample. That is, the children mentioned danger and physiological symptoms of anxiety for scripts with and without evident information of threat, indicating the presence of emotional reasoning and it's association with the normal development (developmental emotional reasoning). The emotional reasoning appeared more perceptible for the context involving social interactions and the factor age interfered in the discriminatory capacity when facing the presence/lack of danger presented in the script. So, the emotional reasoning becomes more complex as the child's cognitive apparatus is improved. The stress scale didn't show any correlation with scripts of the context social interaction. This data indicates that the underlying emotion to certain threatening social contexts may not be fear, but shame and worry. The more frequent physiological symptom was "heart beating very fast", showing that the children in this study have an accurate perception for this specific physiological sign. This data suggests that the attention focused on the physiological symptoms can be in the base of the developmental emotional reasoning. As for the strategies of ER, the data showed that the children used with a larger frequency the strategies of social interaction (context physical integrity) and amusement activities (context social interaction). This indicates that the strategies of ER can be linked to the context of emotion (physical threat and social threat) and that the ER happens in the presence of emotional reasoning. This fact suggests that the developmental emotional reasoning, not only do not interfere in the abilities of the child's ER, but also requires specific repertoires of fear regulation in different contexts. Finally, the answers of strategies of ER, as well as the answers of emotional reasoning (physiological symptoms and danger degree), were not influenced by the sex or intelligence level. All these data lead to the conclusion that the emotional reasoning that canhappen in childhood is linked to normal development. The pathological character of the emotional reasoning cited in the literature could be characterized by the intensification of the experienced emotion (presence of psychopathology) and of the action of cognitive inclinations. In the subsequent phases of development, this phenomenon could reflect an obstacle in the capacity of danger stimuli discrimination, hindering their appropriate perception in the envirenment, as well as the use of appropriate ER strategies in the presence of multiple factors (life history, rich repertoire in escape behaviors and avoidance, etc.).